Perspectives of decisional surrogates and patients regarding critical illness genetic research. Issue 1 (2nd January 2016) - Freeman, Bradley D.; Bolcic-Jankovic, Dragana; Kennedy, Carie R.; LeBlanc, Jessica; Eastman, Alexander; Barillas, Jennifer; Wittgen, Catherine M.; Lindsey, Kathryn; Mahmood, Rumel S.; Clarridge, Brian R.
Abstract: Background: Critical illness research is challenging due to disease severity and because patients are frequently incapacitated. Surrogates called upon to provide consent might not accurately represent patient preferences. Though commonplace, genetic data collection adds complexity in this context. We undertook this investigation to understand whether surrogate decision makers would be receptive to permitting participation in a critical illness genetics study and whether their decision making was consistent with that of the patient represented.Methods: We invited individuals identified as surrogates for critically ill adults, if required, as well as patients once recovered to participate in a survey designed to understand attitudes about genetic research. Associations between dependent (receptivity to participation, concordance of responses) and independent variables were tested using bivariate and multivariate logistic regression analyses.Results: Most members of the entire surrogate sample ( n = 439) reported familiarity with research, including genetic research; tended to view research as useful; and were receptive to allowing their family member participate (with 39.6% and 38.1% stating that this would be "very" and "somewhat likely, " respectively) even absent direct benefit. Willingness to participate was similar comparing genetic and nongenetic studies (χ 2 [1, n = 439] = 0.00127, p = .972), though respondents expressed worry regarding lack of confidentiality of genetic data. Responses were concordant in 70.8% of the 192 surrogate–patient pairs analyzed. In multivariate analysis, African American race was associated with less receptivity to genetic data collection ( p < .05). No factors associated with concordance of surrogate–patient response were identified.Conclusions: Surrogates' receptivity to critical illness research was not influenced by whether the study entailed collection of genetic data. While more than two-thirds of surrogate-patient responses for participation in genetics research were concordant, concerns expressed regarding genetic data often related to breach of confidentiality. Emphasizing safeguards in place to minimize such breeches might prove an effective strategy for enhancing recruitment.